2017
DOI: 10.1007/s00417-017-3816-5
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic optic neuropathy treatment trial (TONTT): open label, phase 3, multicenter, semi-experimental trial

Abstract: EPO, steroid, and observation showed a significant improvement of BCVA in patients with TON. Initial BCVA of NLP and late treatment (>3 days) were significant risk factors for visual improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“… 5 , 8 , 9 Current treatment options for TON include observation, high-dose corticosteroid use, or surgical decompression of the optic canal. 9 13 In a prospective, comparative, nonrandomized interventional study of TON visual outcomes, the International Optic Nerve Trauma Study found that, after adjusting for baseline visual acuity, no clear benefit of either corticosteroid therapy or optic canal decompression surgery was observed. 14 , 15 Hence, effective therapy for visual recovery in TON remains elusive.…”
mentioning
confidence: 99%
“… 5 , 8 , 9 Current treatment options for TON include observation, high-dose corticosteroid use, or surgical decompression of the optic canal. 9 13 In a prospective, comparative, nonrandomized interventional study of TON visual outcomes, the International Optic Nerve Trauma Study found that, after adjusting for baseline visual acuity, no clear benefit of either corticosteroid therapy or optic canal decompression surgery was observed. 14 , 15 Hence, effective therapy for visual recovery in TON remains elusive.…”
mentioning
confidence: 99%
“… 13) The same study group recently showed the effect of intravenous EPO for TON in an open-label, phase 3, multicenter, semi-experimental trial. 14) All three groups (EPO, 69; steroid, 15; observation, 16) showed significant improvement of BCVA in patients with TON. Interestingly, color vision was significantly improved in the EPO group.…”
Section: Treatment Of Indirect Tonmentioning
confidence: 87%
“…A new treatment option for TON is the cytokine hormone erythropoietin (EPO). 13 14) EPO has been reported to be effective for reducing neural apoptosis and protecting brain ischemic injury. 9) A pilot study of intravenous EPO for TON showed a promising result, in that patients in the EPO-treated group showed a significantly better visual outcome than the observation group.…”
Section: Treatment Of Indirect Tonmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Hippocrates first noted visual impairment after facial trauma, 11) numerous reports have described TON, focusing on its causes and methods of treatment. 1,7,[14][15][16][24][25][26] In this article, I review the recent literature regarding TON and discuss how to manage indirect TON.…”
Section: Introductionmentioning
confidence: 99%